Judicial Analysis of Law Enforcement Against Corruption In The Procurement of Goods and Services For Government Interest - Siahaan, Yanti; Esther, July; Debora (Indonesian Journal Publisher, 2025)
This study aims to Corruption in the procurement of goods and services is one of the most common corruption offences, ranking second only to gratuities/bribes. This is based on the World Bank (World Bank), every year more than 10 billion US dollars or around 85 trillion rupiah of the central government budget, both for routine expenditure and development projects, are spent through the procurement of goods and services. The purpose of this study is to find out the effectiveness of legal regulation of corruption offences in the procurement of goods and services for the benefit of the government and to find out to Overcome Obstacles in Law Enforcement of Corruption in the Procurement of Goods and Services for Government Interests so that Corruption Cases Can Decrease. The method used is a qualitative research method with descriptive analysis through legislative, case and conceptual approaches. The result of this research is that the formulation of minimum criminal punishment in Law Number 20 Year 2021 has shortcomings, namely not formulating sentencing guidelines to apply this minimum criminal punishment and efforts to overcome obstacles in law enforcement of corruption in the Procurement of Goods and Services so that the number of cases of Procurement of Goods and Services in the following year can decrease, including The principle of procurement must be carried out in tandem with enforcing integrity and increasing the professionalism of procurement human resources